ANALISIS PENGAKUAN PENDAPATAN DAN BEBAN PADA CV. PUTRA TUNGGAL MANDIRI KABUPATEN NGADA BERDASARKAN PSAK NO.34 - Ari, Yustina Elu; Djou, Laurentius D Gadi; Reo, Hermanus (Jurnal Riset Ilmu Akuntansi, 2020)
The purpose of this study is (1) To determine the recognition of income and expenses in the CV. Putra Tunggal Mandiri. (2) To determine the recognition of income and expenses carried out on the CV. Putra Tunggal Mandiri according to PSAK 34. The data analysis technique used is a descriptive qualitative analysis method of data collected compiled, grouped, and analyzed so that it can provide a true picture of the recognition of income and expenses and see the comparison of recording financial statements conducted by CV. Putra Tunggal Mandiri with PSAK No. 34 The results of this study indicate that (1) CV. Putra Tunggal Mandiri in running a project that is more than one accounting period (long-term construction contract), the company applies the percentage of completion method in recognizing opinions and expenses. (2) The company has not applied it as a basis for the recognition of revenues and expenses, as evidenced in 2018 the company recognizes that revenue is too small. This happens because the company only recognizes revenue worth the project down payment, which is 30% of the total contract value, which is 30% xRp. 199,228,000 = Rp. 59,768,400, according to PSAK No. 34 works were completed in 2018 at 82.3% of the contract value of 82.3% x Rp. 199,228,000 = Rp. 163,964,644 which consists of raw material costs, labor costs and overhead costs. Additional contract costs to Rp. 163,925,000 due to the lack of companies to record the depreciation expense of equipment that is included in the overhead, the burden and revenue recognized too small.